Pengaruh Gaya Kepemimpinan Dan Komitmen Organisasi Terhadap Kepuasan Kerja Serta Dampaknya Terhadap Kinerja Pegawai Pada Kantor Dinas Kependudukan Dan Pencatatan Sipil Kota Jambi - Pantun Bukit; Yunan Surono; Hendro Priono (J-MAS (Jurnal Manajemen dan Sains), 2020)
The purpose of this research is to find out the description of leadership style, organizational commitment, performance and job satisfaction at the Office of the Office of Population and Civil Registry of Jambi City year 2019. To analyze the influence of leadership style and organizational commitment simultaneously and partially both directly and indirectly to job satisfaction at the Office of the Office of Population and Civil Registry of Jambi City year 2019. To analyze the influence of leadership style and organizational commitment simultaneously and partially both directly and indirectly on performance at the Office of The Office of Population and Civil Registry of Jambi City in 2019 and to analyze the influence of leadership style and employee commitment through job satisfaction to performance at the Office of The Office of Population and Civil Registry of Jambi City year 2019. The population of this study was all employees of the Jambi City Civil Registry and Population Office as many as 95 people. The population has a close relationship with the problems studied. Samples are part of the elements of the population to be examined. In this study, probability sampling techniques were used because the population in this study was not very large. Probability sampling is a sampling technique that provides an opportunity for each member of the population to be selected as a sample member. With probability sampling, it is random or random sampling of the existing population. The sample from this study was all employees of the Jambi City Office of Population and Civil Registry as many as 95 people. The leadership style and commitment of the organization simultaneously has a positive and significant influence on job satisfaction in employees of the Office of Population and Civil Registry of Jambi City. Where the influence of leadership style and simultaneous organizational commitment to job satisfaction simultaneously is worth 40.68%. Leadership style and organizational commitment through performance can have a direct and indirect effect on job satisfaction. Where the influence of leadership style on job satisfaction through performance is 14.94%, the effect of orgnaization commitment on job satisfaction through performance of 1.82% and leadership style and organizational commitment together through performance to job satisfaction is 19.97%.